1988
DOI: 10.1093/jac/22.supplement_c.149
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of ofloxacin against infection caused by Neisseria gonorrhoeae and Chlamydia trachomatis

Abstract: Ofloxacin was used to treat patients with gonorrhoea and/or Chlamydia trachomatis infection. Gonorrhoea was treated with a single 400 mg dose and chlamydial infection with a seven day course (200 mg bd). Fifty of 84 patients with gonorrhoea (60 men and 24 women) returned for two follow-up examinations 7 and 14 days after treatment, 17 patients returned for only one follow-up examination and 17 defaulted. Neisseria gonorrhoeae was re-isolated from three patients who had probably become re-infected. Treatment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Interestingly, despite the observation that Chlamydia trachomatis is more susceptible than U. urealyticum to fluoroquinolones in vitro, a higher fraction of patients with nongonococcal urethritis caused by U. urealyticum was cured by norfloxacin (75) and ciprofloxacin (235) than those with Chlamydia trachomatis, and ciprofloxacin appeared to be more effective (P = 0.12) than doxycycline (235). In contrast, ofloxacin (200 mg twice daily) (50, 243,530,622) or fleroxacin (400 to 800 mg per day) (603) given for 5 to 15 days eradicated Chlamydia trachomatis from the urethra or cervix in >90% of patients, a result comparable to that with doxycycline in one study (243). Urethritis that was culture negative for chlamydia responded to ofloxacin less well in men (530).…”
Section: Sexually Transmitted Diseasesmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, despite the observation that Chlamydia trachomatis is more susceptible than U. urealyticum to fluoroquinolones in vitro, a higher fraction of patients with nongonococcal urethritis caused by U. urealyticum was cured by norfloxacin (75) and ciprofloxacin (235) than those with Chlamydia trachomatis, and ciprofloxacin appeared to be more effective (P = 0.12) than doxycycline (235). In contrast, ofloxacin (200 mg twice daily) (50, 243,530,622) or fleroxacin (400 to 800 mg per day) (603) given for 5 to 15 days eradicated Chlamydia trachomatis from the urethra or cervix in >90% of patients, a result comparable to that with doxycycline in one study (243). Urethritis that was culture negative for chlamydia responded to ofloxacin less well in men (530).…”
Section: Sexually Transmitted Diseasesmentioning
confidence: 95%
“…Norfloxacin eradicated equally well N. gonorrhoeae susceptible or resistant to penicillin and produced results comparable to those with spectinomycin in a nonrandomized comparative study (127). Ciprofloxacin (100 to 500 mg) (467,628,677,690,761), ofloxacin (200 to 600 mg) (15,89,622), enoxacin (400 to 600 mg) (552,705,760,802), and fleroxacin (400 mg) (57, 438) in single doses have also been highly effective in curing uncomplicated gonorrhea. Infections involving the urethra or uterine cervix were almost uniformly cured.…”
Section: Sexually Transmitted Diseasesmentioning
confidence: 99%
“…Other open or comparative studies with single doses of norfloxacin (800 mg) (9, 44), ciprofloxacin (100 to 500 mg) (30,48,56), ofloxacin (200 to 600 mg) (3,14,33,42), enoxacin (200 to 600 mg) (4,38,50,55,60), or fleroxacin (400 mg) (8) confirmed the efficacy of fluoroquinolones in the treatment of uncomplicated gonorrhea. Treatment failures for gonococcal urethritis or cervicitis have been rare with these agents, except for patients treated with lower doses of enoxacin.…”
Section: Clinical Efficacy In Genital Tract Infectionsmentioning
confidence: 86%
“…None of the currently available antimicrobial agents, including fluoroquinolones, is effective as a single dose in eradicating C. trachomatis genital infections, which most often occur as the syndrome of nongonococcal urethritis (NGU) or mucopurulent cervicitis. Studies which used single doses of norfloxacin (44), ciprofloxacin (30,43,48), ofloxacin (6,42), enoxacin (55,60), or fleroxacin (29) for the treatment of gonorrhea uniformly reported the substantial persistence of C. trachomatis or the development of postgonococcal urethritis (3,9,38,46,56), which is often caused by C. trachomatis.…”
Section: Clinical Efficacy In Genital Tract Infectionsmentioning
confidence: 99%
“…The serum peak level after 500 mg per os is about 10 pg/ml [19], and ofloxacin serum levels of 1 pg/ml can easily be maintained in hu mans [19]. Clinical studies have shown that ofloxacin given as a 7-day course is effective in the treatment of chlamydial in fections [20,21], Ofloxacin is also active against Mycoplasma hominis and other Mycoplasma sp. [22].…”
Section: Discussionmentioning
confidence: 99%